Assessment of potential ecological risk of microplastics in the coastal sediments of India: A meta-analysis - M. Ranjani (9648983) (2021)
Abundance, chemical composition and ecological risk of microplastics (MPs) in terrestrial and marine environments have merited substantial attention from the research communities. This is the first attempt to comprehend the ecological risk of MPs in sediments along the Indian coast using meta-data. Polymer hazard index (PHI), pollution load index (PLI) and potential ecological risk index (PERI) were used to evaluate the quality of sediments. Areas have high PHI values (>1000) due to the presence of polymers with high hazard scores such as polyamide (PA) and polystyrene (PS). According to PLI values, sediments along the west coast of India (WCI) are moderately contaminated with MPs (PLI: 3.03 to 15.5), whereas sediments along the east coast of India (ECI) are less contaminated (PLI: 1 to 6.14). The PERI values of sediments along the Indian coast showed higher ecological risk for the metropolitan cities, river mouths, potential fishing zones and the remote islands. Other Information Published in: Marine Pollution Bulletin License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.marpolbul.2021.111969